Escherichia coli in betel leaves: prevalence, virulence characterization and antibiogram (Asian-Australasian Journal of Bioscience and Biotechnology, 2024)
Escherichia coli is a significant foodborne pathogen, frequently linked to hemorrhagic diarrhea, especially in developing nations, where it presents considerable public health concerns. This study was conducted to examine the virulence gene profiles and antibiotic resistance patterns of E. coli strains isolated from piper betel leaves. A total of 100 betel leaf samples, including fresh (n = 60) and ready-to-eat (n = 40) specimens, were collected and tested for the presence of E. coli using standard diagnostic techniques, such as selective culture methods, staining, latex agglutination, and polymerase chain reaction (PCR) assays. Further, the identified E. coli isolates underwent PCR-based testing for virulence genes and disk diffusion assays to assess antibiotic susceptibility. Among the 100 samples screened, 4% (n = 4/100; 95% CI: 1.57–9.84; P = 0.1126) were identified as E. coli O157, and 33% (n = 33/100; 95% CI: 24.56–42.69; P = 0.4011) were classified as non-O157 isolates. The virulence gene stx1 was found in 10.81% of isolates, while stx2, eaeA, and hlyA genes were not detected in any samples. Antibiotic resistance analysis showed that all isolates (100%, 37/37) were resistant to amoxicillin and erythromycin, with 75.68% (28/37) demonstrating resistance to tetracycline. Notably, all isolates were fully susceptible to ceftriaxone and ciprofloxacin. A majority (72.97%, 27/37) of isolates were sensitive to streptomycin, and 67.57% (25/37) were sensitive to gentamicin. Additionally, 86.48% of the E. coli isolates exhibited multidrug resistance (MDR), showing 10 resistance patterns, including 8 MDR patterns. The most common MDR pattern was AMX-TE-E, observed in 56.76% (21/37) of isolates. One isolate demonstrated resistance to six of the eight tested antibiotics across four distinct classes, with the resistance pattern AMX-TE-GEN-S-E-AZM. The MAR indices for E. coli isolates ranged between 0.25 and 0.75. These findings highlight the significant threat posed to global public health by multidrug-resistant shiga toxin-producing E. coli found on piper betel leaves in urban environments.Asian Australas. J. Biosci. Biotechnol. 2024, 9(3), 33-44